D-hyponormal and D-quasi-hyponormal Operators - Mesbah, Nadia; Messaoudene, Hadia (Communications in Mathematics and Applications, 2022)
New classes of operators named D-hyponormal, and D-quasi-hyponormal are introduced in this paper. Some basic properties of these operators are presented. An investigation of extensions of the Fuglede-Putnam theorem for D-hyponormal operators is given.
Keywords: Drazin inverse; D-hyponormal operator; D-quasi-hyponormal operator; Fuglede-Putnam theorem